2003
DOI: 10.1002/jez.a.10256
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cortisol on osmoregulation and energy metabolism in gilthead seabream Sparus aurata

Abstract: Gilthead seabream Sparus aurata were injected intraperitoneally with slow-release implants of coconut oil alone or containing cortisol (50 and 100 microg x g(-1) body weight), and sampled after two, five, and seven days to assess the simultaneous effects of cortisol on both osmoregulation and energy metabolism. Plasma cortisol levels increased in treated fish to 50-70 ng x ml(-1). An enhanced hypoosmoregulatory capacity of cortisol-implanted fish is suggested by the increase observed in gill Na+, K+-ATPase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
73
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 45 publications
10
73
2
Order By: Relevance
“…In addition to its glucocorticoid actions, the role of cortisol as a mineralocorticoid is obvious in S. senegalensis, as cortisolinjected animals showed lowered plasma Na C and Cl K levels and increased Na C , K C -ATPase activities in gills and kidney 3 days after injection. These results agree with the classical osmoregulatory role of cortisol in teleosts (Seidelin et al 1999, Laiz-Carrión et al 2003, Sherwani & Parwez 2008.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to its glucocorticoid actions, the role of cortisol as a mineralocorticoid is obvious in S. senegalensis, as cortisolinjected animals showed lowered plasma Na C and Cl K levels and increased Na C , K C -ATPase activities in gills and kidney 3 days after injection. These results agree with the classical osmoregulatory role of cortisol in teleosts (Seidelin et al 1999, Laiz-Carrión et al 2003, Sherwani & Parwez 2008.…”
Section: Discussionsupporting
confidence: 91%
“…The use of coconut oil as a vehicle for i.p. hormonal implants has been shown to be an effective and practical method to raise plasma cortisol or thyroid hormone levels in different teleost species (Laiz-Carrión et al 2003, Morgado et al 2007. Nine fish did not receive any treatment and served as the pre-injection group.…”
Section: Experimental Designmentioning
confidence: 99%
“…The reduction in liver and muscle lipid content in the cortisol-treated fish is consistent with the increased lypolytic capacity of chronically stressed fish (Mommsen et al 1999). Cortisol may deplete lipid reverses in fish by increasing the activity of various lipases (Sheridan 1986, Baltzegar et al 2014) and glycerol utilization (Vijayan et al 1991), and by reducing the lipogenic potential of the liver (Vijayan et al 1990, Laiz-Carrió n et al 2003, Ló pez-Patino et al 2014. Moreover, given the known lipolytic properties of GH in the liver (Björnsson et al 2002), our results suggest that cortisol may also promote lipolysis via its stimulatory effects on liver ghr2 expression.…”
Section: Discussionmentioning
confidence: 57%
“…However, whether cortisol has a direct glycolytic effect on the liver is equivocal. Previous studies in fish have shown that cortisol exposure can increase, decrease, or have no effect on liver glycogen content and there is generally no consensus as to the role of cortisol in liver glycogen metabolism (Mommsen et al 1999, De Boeck et al 2001, Laiz-Carrió n et al 2003. In tilapia (O. mossambicus), while injections of both cortisol and leptin increase plasma glucose levels, only leptin decreases liver glycogen content (Baltzegar et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, cortisol was found to upregulate sbGHR1 expression but not sbGHR2 in black seabream. It has been reported recently that cortisol could elicit metabolic changes in seabream liver by decreasing the glucose-6-phosphate dehydrogenase (G6PDH) activity (Laiz-Carrion et al 2003). The enhanced expression of sbGHR1 by cortisol might provide a possible explanation for this report since GH has been shown to reduce hepatic G6PDH activity in fish (Leena et al 1999).…”
Section: Discussionmentioning
confidence: 62%